Workers Awareness and Understanding of Labor Rights and Obligations in the Workplace - Simangunsong, Michelle; Simanjuntak, Putri Natalia; Rayhan, Ahmad; Pahlevi, Habieb; Gurung, Lina; Riady, Yasir; Ajmal, Muhammad (CV Media Inti Teknologi, 2025)
Background of study: Workers’ awareness of their rights and obligations within Indonesia’s employment social security system remains relatively low, particularly among informal workers. Although BPJS Ketenagakerjaan provides comprehensive protection against occupational risks, many workers still lack a clear understanding of program benefits and participation requirements, limiting the effectiveness of national social protection efforts. Aims and scope of paper: This paper examines the role of BPJS Ketenagakerjaan in improving workers’ awareness of their rights and obligations as participants in employment-based social security. The study explores existing outreach strategies, levels of worker literacy, barriers to participation, and the implications for overall social protection. Methods: A qualitative literature review method was employed by synthesizing secondary data from academic articles, government regulations, and BPJS Ketenagakerjaan reports published within the last ten years. The analysis identifies recurring issues related to worker knowledge, program implementation, and institutional challenges. Result: The findings show that BPJS Ketenagakerjaan plays an important role in disseminating information, expanding membership, and improving service accessibility. However, workers’ understanding of program benefits remains limited, participation in the informal sector is relatively low, and employer compliance is often inconsistent. Existing socialization efforts have not fully closed the awareness gap, especially among vulnerable worker groups. Conclusion: The study concludes that improving workers’ awareness requires more targeted and continuous education programs, stronger employer enforcement, and broader collaboration among government institutions. Enhancing literacy and participation is essential to achieving more comprehensive and equitable labor protection in Indonesia.